Microwave ablation of a solitary colorectal liver metastasis complicated by stomach perforation and gastrocutaneous fistula - a case report - Symeonidis, S; Giankoulof, C; Christidis, P; Anestiadou, E; Loutzidou, L; Bitsianis, S; Ioannidis, O; Tsalis, K; Angelopoulos, S; Petsatodis, E (Klinicka onkologie, 2022)
BACKGROUND: Organ perforation secondary to thermal ablation is a rare but severe complication that can occur in certain patients, in whom tissue dissection and preservation cannot be adequately achieved. CASE DESCRIPTION: A 69-year-old man presented with a gastrocutaneous fistula 20 days after a microwave ablation of liver metastases from colorectal cancer. Besides skin rash, local tenderness, and gastric content discharge from a wound where the probe had been placed, no other signs or symptoms were present. The patient was treated surgically, and a wedge-shaped gastric resection was performed. His postoperative course was uneventful. After 8 months, the patient underwent the same procedure for local progression of the same lesion, using a pulsed MW antenna and a dedicated hydrodissection needle, without complications. CONCLUSIONS: A gastrocutaneous fistula is a rare complication of microwave ablation. However, adequate hydrodissection can minimize the risk for the development of these complications. Proper treatment of these complications does not preclude repeated usage of microwave ablation in the future.
Keywords: senioři; Liver Neoplasms; mikrovlny; nádory jater; kolorektální nádory; microwave ablation; výsledek terapie; gastric perforation; Colorectal Neoplasms; mužské pohlaví; píštěl žaludku; Stomach; žaludek; Humans; Microwaves; liver; Gastric Fistula; gastrocutaneous fistula; Aged; Treatment Outcome; thermal injury; lidé; Male